Vegetation–edaphic correlation and importance value index in Himalayan ‘ecotone’ temperate conifer forest using the multivariate technique - Ali, F.; Zeb, M.; Amin, M.; Rajpar, M.N.; Hidayat, S.; Khan, W.R. (Elsevier, 2024)
Himalayan ‘Ecotone’ temperate conifer forest is the cradle of life for human survival and wildlife existence. In spite of the importance of these areas, they have not been studied in depth. This study aimed to quantify the floristic structure, important value index (IVI), topographic and edaphic variables between 2019 and 2020 utilizing circular quadrant method (10 m x 10 m). The upper-storey layer consisted of 17 tree species belongs to 12 families and 9 orders. Middle-storey shrubs comprised of 23 species representing 14 families and 12 orders. A total of 43 species of herbs, grasses, and ferns were identified from the ground-storey layer, representing 25 families and 21 orders. Upper-storey vegetation structure was dominated by Pinus roxburghii (22.45 %) and middle-storey by Dodonaea viscosa (7.69 %). However, the ground layer vegetation was diverse in species composition (43 species) and distribution. The floral vegetation structure was encompassing of three floral communities which were diverse in IVI, such as, in Piro–Aial (Group 2), Pinus roxburghii (54.46 x 15.94) had the highest IVI value, followed by Pinus wallichiana (45.21 x 14.85) in Piwa–Quin (Group 3) and Ailanthus altissima (22.84 x 19.25) in Aial–Qugal (Group 1). However, the IVI values for Aesculus indica, Celtis australis, and Quercus incana in Aial–Qugal (Group 1) were not determined due to low detection rate. Nevertheless, eleven of these species showed 0 IVI values in Piro–Aial (Group 2) and Piwa–Quin (Group 3). CCA ordination biplot illustrated the significant differences among floral communities and its distribution, which impacted by temperature, rainfall, soil pH, altitude, and topographic features. Ward's agglomerative clustering finding reflected 'Ecotone' temperate conifer forest is rich and diverse floristic structure.